2003
DOI: 10.1007/s00198-003-1403-6
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and health beliefs of women towards osteoporosis

Abstract: A population-based survey was conducted to determine the awareness, knowledge of risk factors, and attitudes toward osteoporosis in middle-aged and elderly women in Singapore. Chinese women aged 45 years and above ( n=1,376) living in Teban Gardens (community on the western side of Singapore) were randomly sampled. Household interviews were conducted and questions on socioeconomic status, knowledge of osteoporosis, identification of risk factors for osteoporosis, and health beliefs were assessed. There were 94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
54
0
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 8 publications
13
54
0
7
Order By: Relevance
“…Similarly, other study found that better educated Chinese women in Singapore seem to know more about osteoporosis than those ones worst educated [22]. A previous study has likewise found that osteoporosis-related knowledge is independent of age [11].…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, other study found that better educated Chinese women in Singapore seem to know more about osteoporosis than those ones worst educated [22]. A previous study has likewise found that osteoporosis-related knowledge is independent of age [11].…”
Section: Discussionmentioning
confidence: 74%
“…Similar results were attained in African-American, Canadian and Chinese women, with whom television and radio were the most important sources. [24][25][26] Thus, it is vital that health professionals at the primary healthcare level provide women with relevant effective health education programs, enabling them to recognize the vague and nonspecific symptoms of osteoporosis as well as learn more about the risk factors of osteoporosis to avoid them. Moreover, health professionals have a responsibility to identify high-risk patients to achieve the goals of prevention, early detection, and appropriate treatment.…”
Section: Knowledge About Osteoporosismentioning
confidence: 99%
“…10 Riaz et al also reported higher knowledge about osteoporosis in educated Pakistani women. 11 Another study also showed significantly lower awareness in women (aged 16-49 years) belonging to lower socioeconomic and less educated group.…”
Section: Discussionmentioning
confidence: 91%